2019
DOI: 10.1523/eneuro.0277-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

The Role of BTBD9 in Striatum and Restless Legs Syndrome

Abstract: Restless legs syndrome (RLS) is a sensory-motor neurological disorder characterized by uncomfortable sensations in the extremities, generally at night, which is often relieved by movements. Genome-wide association studies (GWAS) have identified mutations in BTBD9 conferring a higher risk of RLS. Knockout of the BTBD9 homolog in mice (Btbd9) and fly results in motor restlessness and sleep disruption. Clinical studies have found RLS patients have structural and functional abnormalities in the striatum; however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 88 publications
(109 reference statements)
1
23
0
Order By: Relevance
“…BTBD9, a BTB domain-containing protein, is significantly associated with susceptibility to sleep disturbance and restless leg syndrome (RLS). [37][38][39][40] However, there has been no study about its role in cancer or its role as an adaptor of CRL3 E3 ligases that modulates the degradation of tumor suppressors or oncoproteins. In this study, BTBD9 was first identified as an adaptor of CRL3 that regulates the ubiquitination and degradation of its substrate protein TNFAIP1, as demonstrated by the following: (1) TNFAIP1 and BTBD9 interacted, (2) downregulation of BTBD9 delayed the turnover of TNFAIP1, and (3) BTBD9 knockdown diminished the polyubiquitination of TNFAIP1.…”
Section: Discussionmentioning
confidence: 99%
“…BTBD9, a BTB domain-containing protein, is significantly associated with susceptibility to sleep disturbance and restless leg syndrome (RLS). [37][38][39][40] However, there has been no study about its role in cancer or its role as an adaptor of CRL3 E3 ligases that modulates the degradation of tumor suppressors or oncoproteins. In this study, BTBD9 was first identified as an adaptor of CRL3 that regulates the ubiquitination and degradation of its substrate protein TNFAIP1, as demonstrated by the following: (1) TNFAIP1 and BTBD9 interacted, (2) downregulation of BTBD9 delayed the turnover of TNFAIP1, and (3) BTBD9 knockdown diminished the polyubiquitination of TNFAIP1.…”
Section: Discussionmentioning
confidence: 99%
“…Six Meis1 KO males and five WT males with an average age of 9 months were tested in the continuous open field experiment as previously described (Lyu, DeAndrade, et al, 2019, 2020; Lyu, Doroodchi, Xing, et al, 2020; Lyu, Xing, et al, 2019; Lyu, Xing, DeAndrade, Perez, Yokoi, et al, 2020; Lyu, Xing, DeAndrade, Perez, Zhang, et al, 2020). The sample size was determined according to (Lyu, Xing, et al, 2019). The average weight of the animals is 34.5 g. Briefly, mice were maintained on a 12 LD cycle for 7 days in the VersaMax Legacy Open Field activity box (Omnitech Electronics, year of purchase, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Recordings of dopamine neurons were performed with three Meis1 KO males and three WT males with an average age of 10 months (Lyu, Doroodchi, Xing, et al, 2020). The sample size was determined according to (Lyu, Xing, et al, 2019 and 10 glucose, pH = 7.3 with KOH, osmolality = 290-300 mOsm).…”
Section: Electrophysiological Recordingmentioning
confidence: 99%
“…Heterozygous Btbd9 KO (Lyu et al, 2019) were bred with Meis1 KO animals (Meneely et al, 2018) to generate double heterozygotes, which were bred with heterozygous Btbd9 KO mice to generate experimental mice. Behavioral tests were conducted as described (Lyu et al, 2019) and analyzed by SAS GENMOD or mixed model ANOVA. Western blot and quantitative RT-PCR were performed and analyzed as described (Yokoi et al, 2015) using striatal tissues (supplementary material).…”
Section: Objectivementioning
confidence: 99%
“…What does "4 repeats for each genotype" mean? Does this mean the last 4 days that were used in the analysis according to Lyu et al 2019 or did the mice spend four times seven days in the running wheel?…”
Section: Commentmentioning
confidence: 99%